Office activities performance as a mediator between organizational drivers and firm performance: Evidence from Vietnamese SMEs - Minh, Dinh Hoang; Cuong, Tran; Bac, Duong Dinh; Chinh, Tran Thi Quy (The Economics and Finance Letters, 2025)
Office activities performance is a critical but underexplored component of business operations, particularly among small and medium-sized enterprises (SMEs) in Vietnam, an emerging market. This study aims to evaluate both the direct effects of internal and external factors on office activities performance and, more importantly, to assess its mediating role in the relationship between these factors and overall firm performance. Grounded in the Resource-Based View (RBV) and Stakeholder Theory, the proposed model positions leadership as a key driver of internal capabilities, including organizational culture, technological capability, and financial capability, while also accounting for external stakeholder pressures such as government support and customer pressure. Data were collected from 209 SMEs across Vietnam and analyzed using partial least squares structural equation modeling (PLS-SEM) via SmartPLS software. The results reveal that both internal drivers and external pressures significantly and positively influence office activities performance, which in turn mediates their impact on firm performance. These findings emphasize the strategic role of office operations as an intermediary mechanism that connects organizational resources and stakeholder engagement to business outcomes. The study provides theoretical contributions to office management literature and offers practical guidance for SME leaders aiming to strengthen operational effectiveness and competitiveness through enhanced office performance.